PS02.252: LAPOROSCOPIC ADJUSTABLE GASTRIC BANDING: AN UNDERESTIMATED RISK FACTOR FOR THE DEVELOPMENT OF ESOPHAGEAL CANCER?–A NATIONWIDE SURVEY. (5th March 2019) - Gehwolf, Philipp; Kienzl-Wagner, Katrin; Cakar-Beck, Fergül; Schäfer, Aline; Wykypiel, Heinz
Abstract: Background: Among the population of Austria (8, 4 Mill.) about 870.000 (12%) have a body mass index (BMI) > 30 kg/m 2 . For those with morbid obesity, Bariatric surgery is currently the only effective treatment in the long term. In 1994 the laparoscopic adjustable gastric banding (LAGB) was introduced in Austria and about 10.300 patients received it so far. One of our LAGB-patients developed adenocarcinoma of the distal esophagus after 13 years. In order to calculate if patients after LAGB are at higher risk for carcinoma of the esophagus, we performed a nationwide survey. Methods: A questionnaire was sent to all surgical departments in Austria, primarily in order to detect cases with esophageal carcinoma after LAGB, but also to evaluate the policy in Austria concerning the preoperative work-up, the operation and the follow-up in LAGB patients. Results: Since 1994, 37 out of 119 surgical departments in Austria have been performing about 10300 LAGB implantations in total. Moreover, eight surgical departments are performing resective esophageal cancer surgery. Seven patients could be identified with development of upper gastrointestinal malignoma/dysplasia after LAGB implantation. Conclusion: To our knowledge less than 20 cases of esophageal cancer after laparoscopic adjustable gastric banding have been described so far, but there is sound evidence that the development of Barrett's metaplasia after LAGB is much higher The most recent nationwide Austrian statistical report on esophageal cancer (2015) shows an incidence of 8, 8: 100.000/per year, les than 1% of the annually emerging malignant tumors. About 48% of the emerging malignant tumors are squamous cell carcinoma (male: 47, 6%, female: 48, 3%) whereas about 30% are adenocarcinoma (male: 32, 6%; female: 25, 3%). Our data suggests that the incidence for developing an adenocarcinoma of the esophagus in Austria is currently about 3/100.000/a. Compared to the five patients we detected, the incidence of developing a carcinoma of the esophagus after LAGB is about up to fthree fold higher. In patients with a laparoscopic adjustable gastric banding, a diligent preoperative evaluation and aggressive postsurgical follow-up including gastroscopy and in selected cases esophageal manometry seems mandatory. Disclosure: All authors have declared no conflicts of interest.